2019
DOI: 10.1182/bloodadvances.2019000458
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of stage I/II follicular lymphoma in the PET era: an international study from the Australian Lymphoma Alliance

Abstract: Key Points Practices in early-stage FL are variable and include radiation alone, systemic therapy, CMT, or observation. Each practice resulted in similar excellent outcomes; randomized trials are required to determine the optimal treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 33 publications
0
22
0
Order By: Relevance
“…There is also the ongoing debate regarding the optimal therapeutic sequencing approach, to both maximize durable response and quality of life. Finally, the most important question in FL is whether targeted therapy offers the possibility of high rates of cure not just in early but also advanced-stage disease [ 142 ]. That we can now plausibly ask such questions suggests that the future is bright for the management of FL.…”
Section: Discussionmentioning
confidence: 99%
“…There is also the ongoing debate regarding the optimal therapeutic sequencing approach, to both maximize durable response and quality of life. Finally, the most important question in FL is whether targeted therapy offers the possibility of high rates of cure not just in early but also advanced-stage disease [ 142 ]. That we can now plausibly ask such questions suggests that the future is bright for the management of FL.…”
Section: Discussionmentioning
confidence: 99%
“…The impact on cost-effectiveness of both short and long-term toxicities is often burdened by decreased quality of life, which is reflected in the disutility assigned to both the ‘failure’ health state and the disutility applied in the simulation during treatment periods. We used an average cost of commonly used systemic regimens (BR, R-CHOP, R-CVP and rituximab monotherapy) reflecting variable clinical practice and similar PFS among therapies from previous datasets (9, 14).…”
Section: Discussionmentioning
confidence: 99%
“…It raises the question of whether localized presentation is a matter of chance (i.e., incidental early identification of a process bound to disseminate with time) or represents an inherent biological property “directing” lymphoma to a distinct region. The latter hypothesis is supported by similarly low rates of progression in rigorously staged patients with localized follicular lymphoma (FL) treated with observation compared with radiotherapy (RT) [ 20 ]. Further, several studies have suggested that localized FL is often characterized by a unique genetic profile, lower rates of BCL2/IGH translocation and a higher dependence on local microenvironmental features [ 21 24 ].…”
Section: Localized Diseasementioning
confidence: 99%
“…However, a SEER analysis of 6568 patients with localized grade 1–2 FL found that upfront RT was associated with improved disease-specific survival (DSS) and overall survival (OS) compared to patients who did not receive RT (10 y and 20 y DSS 79% and 63% for RT vs. 66% and 51% for no RT) [ 45 ]. In contrast, several reports suggested similar OS for upfront RT compared with observation; most notably, a multicenter retrospective review of 256 patients with FL rigorously staged with PET and a BM biopsy and treated with RT ( n = 171) or watchful waiting (WW) ( n = 85) demonstrated no difference in the time to first chemotherapy (TTC) treatment (4-year TTC 75–80%) [ 20 , 37 , 46 , 47 ].…”
Section: Localized Diseasementioning
confidence: 99%